Implementation of Education for Sustainability in Turkish Pre-Service Teachers' Practicum - Sule ALICI; Havva Ayca ALAN (Brock University, 2022)
In this study, we explored early childhood education pre-service teachers' (ECEPTs') understanding and pedagogical application of education for sustainability (EfS) by critically analyzing EfS implementation during ECEPTs' practicum. The study examined the challenges and critical aspects of EfS practices in the practicum, and the relationships among mentor teachers, academic mentors, and ECEPTs. A multiple case study methodology was employed involving two purposefully distinct universities with 14 participant students across the two university case study sites. Initially, 22 practicum activity plans for each ECEPT were examined via content analysis; then, the students were individually interviewed about the plans and their implications. Subsequent analysis indicated negligible differences between the two universities' student activity plans regarding quality (aspects of EfS) and quantity (frequency of EfS activities). The students self-reflected about their EfS understandings and implementation. Additionally, they remarked that academic mentors' and mentor teachers' stances influenced them either positively or negatively during their workplace-based learning. They also pointed to the absence of a whole-institution approach, not only at the practicum school but also at the university level.